A systematic analysis of doctoral publication trends in South Africa - van Schalkwyk, Susan; Mouton, Johann; Redelinghuys, Herman; McKenna, Sioux (South African Journal of Science, 2020)
It is incumbent upon doctoral students that their work makes a substantive contribution to the field within which it is conducted. Dissemination of this work beyond the dissertation, whether whilst studying or after graduation, is necessary to ensure that the contribution does not remain largely dormant. While dissemination can take many forms, peer-reviewed journal articles are the key medium by which knowledge is shared. We aimed to establish the proportion of doctoral theses that results in journal publications by linking South African doctoral thesis metadata to journal articles authored by doctoral candidates. To effect this matching, a customised data set was created that comprised two large databases: the South African Theses Database (SATD), which documented all doctoral degrees awarded in South Africa (2005–2014), and the South African Knowledgebase (SAK), which listed all publications submitted for subsidy to the South African Department of Higher Education and Training (2005–2017). The process followed several iterations of matching and verification, including manual inspection of the data, in order to isolate only those records for which the link was established beyond doubt. Over the period under review, 47.6% of graduates, representing 22 of the 26 higher education institutions, published at least one journal article. Results further indicate increasingly higher publication rates over time. To explore whether the journal article identified was a direct product of the study, a similarity index was developed. Over 75% of records demonstrated high similarity. While the trend towards increasing publications by graduates is promising, work in this area should be ongoing.Significance:• In spite of increasing trends in publications by graduates, many are not disseminating their work, suggesting that significant bodies of research are potentially not being shared with the academic community and are therefore not contributing to the relevant discipline or field.• This study provides baseline data from which a number of further investigations can be launched, such as exploring the extent to which doctoral candidates who are also academics are publishing their work; the factors that enable or constrain publication; the other avenues of dissemination used; and whether publishing or not publishing can serve as a proxy for the quality of the doctoral work.